The effects and mechanism of urease inhibitor and its combination with nitrification inhibitor on nitrous oxide emission across four soil types - Liu, Churong; Li, Benjie; Wu, Qihua; Chen, Diwen; Zhou, Wenling; Ao, Junhua (Frontiers in Plant Science, 2025)
Nitrogen (N) fertilization is essential for ensuring crop productivity, while excessive N application significantly increases greenhouse gases (GHGs) emissions, particularly nitrous oxide (N2O). Urease inhibitors (UI) and combined urease and nitrification inhibitors (UN) have demonstrated potential in mitigating GHGs emission, though their efficiency with great variation across different soils types. In this study, controlled incubation experiments were conducted using four types of agricultural soils to evaluate the mitigation potential of UI and UN application and to investigate their underlying mechanisms. N fertilization significantly increased N2O emissions by 5.1 99.9-fold and elevated CO2 emissions by 13.6 65.4% across all soil types. The UI treatment decreased the peak of NO2– concentrations in two alkaline soils, while the UN treatment decreased both NO2– and NO3– concentrations in all four soils. In terms of GHG mitigation, UI treatment reduced N2O emissions by 16.5 57.4% in alkaline soils and reduced CO2 emissions by 6.5 49.3% across four soil types. The UN treatment demonstrated superior efficacy, reducing N2O emissions by 52.5 92.4% and CO2 emissions by 4.2 87.2% across all soils. Metagenomic sequencing revealed that both UI and UN significantly inhibited the relative abundances of key functional genes associated with nitrification (hao and nxrAB), dissimilatory nitrate reduction (narGHI/napAB), nitrite reduction (nirS/nirK), and nitric oxide reduction (norBC). Random forest identified key factors influencing the N2O mitigation efficiency of UI and UN. These included soil properties such as soil pH, total nitrogen, organic matter, available potassium, water-filled pore space, texture. Additionally, partial functional genes related to nitrification, denitrification, carbon and methane metabolism, sulfur and phosphorus cycling were also identified as key contributors. Overall, these findings provide valuable insights for the region-specific application of UI and UN to effectively mitigate GHGs emissions. The identification of key soil abiotic and biotic factors offers a theoretical foundation for optimizing inhibitors application and enhancing their mitigation efficiency.